The effect of financial literacy on teachers’ personal financial management in Westrand schools - Budhoo, Pranaksha (University of the Witwatersrand, Johannesburg, 2022)
This research study examines the impact of financial literacy, financial behaviour, and financial wellbeing on educators' financial management, with a specific focus on exploring whether higher levels of education equate to higher levels of financial literacy. Educators play a critical role in society but often face challenges in effectively managing their finances. The objective of this study is to investigate whether educators with higher levels of education possess higher levels of financial literacy, and how financial behaviour and financial wellbeing are influenced. Using a mixed-methods approach, the study collects quantitative data through surveys to measure financial literacy, financial behaviour, and financial wellbeing among a sample of educators. Additionally, qualitative interviews are conducted to gain deeper insights into the experiences, attitudes, and challenges related to personal finances among educators. Preliminary findings suggest that higher levels of education do not necessarily equate to higher levels of financial literacy among educators. Despite having advanced degrees, educators may still exhibit gaps in financial knowledge and understanding. Furthermore, the study reveals that financial behaviour and financial wellbeing are influenced by factors beyond formal education, such as personal experiences, socioeconomic background, and access to financial resources. These findings have significant implications for educational institutions and policymakers. Efforts to improve educators' financial management should focus on targeted financial literacy programs that address specific knowledge gaps and provide practical tools and resources. Additionally, support systems should be established to promote positive financial behaviour and enhance financial wellbeing among educators, considering the diverse factors that influence their financial decision-making processes. By addressing the unique challenges faced by educators in their personal financial management, educational institutions and policymakers can empower them to make informed financial decisions, improve their financial outcomes, and ultimately contribute to their overall job satisfaction, well-being, and effectiveness in the education system
A research report submitted in partial fulfillment of the requirements for the degree of Master of Master of Business Administration to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2022
Keywords: Financial literacy; Financial behaviour; Financial wellbeing; Financial managemen; UCTD; SDG-4: Quality education